Financial satisfaction and financial stressors in marital satisfaction. - Archuleta, Kristy L.; Britt, Sonya L.; Tonn, Teresa J.; Grable, John E. (My University, 2011)
Using a sample of 310 married respondents from one U.S. Midwestern state, a test was conducted to examine the association of financial satisfaction and financial stressors in a spouse’s decision to stay married to the same person or leave the relationship. The role of demographic and socioeconomic variables, religiosity, psychological constructs, financial satisfaction, and financial stressors as factors influencing marital satisfaction was tested. Financial stressors were measured using a list of financial stressors adapted from the literature. Financial satisfaction was measured with a one-item scale for financial satisfaction. The Kansas Marital Satisfaction scale was used as a validation tool to assess whether individuals would marry or not marry again. Religiosity and financial satisfaction were positively associated with marital satisfaction. A negative interaction between financial satisfaction and financial stressors was also noted. Findings suggest that respondents who are financially satisfied tend to be more stable in their marriages.
Keywords: Financial satisfaction; Financial stressors; Marital satisfaction